Spolek československých advokátů v zahraničí během druhé světové války - David Hubený (Právněhistorické studie, 2023)
The article deals with the Association of Czechoslovak Advocates Abroad in Exile in Great Britain during the Second World War, its rights and aspects of life in exile. Attention is paid to the tasks arising from cooperation with the Czechoslovak government in exile.